Brazil: Women and legislation against racism. Women´s rights are human rights / Leila Linhares Barsted, Jacqueline Hermann, María Elvira Vieira d Mello - Linhares Barsted, Leila [et.al] (2001)
Black women and the need for specific judicial demands, black and indigenous women, law vs. reality, economics integration, human rights and racism, international convertion on the elimination of all forms of racial discrimination 1965, convention on the elimination of all forms of discrimination against women, optional protocol to the convention on the elimination of all forms of discrimination against women, convention 111 concerning discrimination in respect of employment and occupation, convention 169 concerning indigenous and tribal peoples in independent countries1989.